The relationship between teacher professional identity and burnout amid the pandemic: A moderated mediation model - Lin, Yishan; Ameyaw, Moses A.; Zhang, Qinhan; Sun, Binghai; Li, Weijian (Frontiers in Public Health, 2022)
Background: Teacher burnout is affected by personal and social factors. COVID-19 has greatly impacted teachers’ physical and mental health, which could aggravate teacher burnout. Purpose: Based on the JD-R model, this study aims to investigate the relationship between teacher professional identity (TPI) and job burnout during the COVID-19 pandemic, and examine the moderating roles of perceived organizational support (POS) and psychological resilience (PR) in these relationships among primary and secondary school teachers in China. Method: A total of 3,147 primary and secondary school teachers participated in this study. Findings: Work engagement played a mediating role in the relationship between professional identity and burnout; when the POS and PR scores were high, the predictive coefficient of TPI on burnout was the largest. Originality: This study tested the mechanism underlying the relationship between TPI and burnout, and explored the protective factors of burnout. Implications: This study supports the applicability of the JD-R model during COVID-19 and provides ideas for teachers to reduce burnout.